Analisis Gaya Bahasa Dan Kata Konkret Pada Puisi “Doa Orang Sibuk Yang 24 Jam Sehari Berkantor di Ponselnya” Karya Joko Pinurbo - Syifa Nurjamilah; Sri Yulistiani Viranti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is entitled Analysis of Language Style and Concrete Words in the Poem “Doa Orang Sibuk yang 24 Jam Sehari Berkantor Di Ponselnya” by Joko Pinurbo. This research is a form of appreciation for literary works in the context of understanding language styles and concrete words in poetry. This study aims to describe and interpret the use of language style and concrete words in the poem titled “Doa Orang Sibuk yang 24 Jam Berkantor Di Ponselnya” by Joko Pinurbo. According to Sudjiman, language style includes diction or lexical choice, sentence structure, majas and imagery, rhyme patterns, and matra found in literary works (1987: 13) while concrete words are words that can be described concretely by the reader's mind when reading a poem. The method used in this research uses a qualitative method by investigating the language style and concrete words in the poem “Doa Orang Sibuk yang 24 Jam Sehari Berkantor di Ponselnya” by Joko Pinurbo so as to produce concrete data. With this research, it can produce data that can find out the language style and concrete words used in the poem “Doa Orang Sibuk yang 24 Jam Sehari Berkantor di Ponselnya” by Joko Pinurbo.